2021
DOI: 10.1007/s11606-020-06589-1
|View full text |Cite
|
Sign up to set email alerts
|

Home Telemonitoring to Reduce Readmission of High-Risk Patients: a Modified Intention-to-Treat Randomized Clinical Trial

Abstract: BACKGROUND: Home telemonitoring has been used with discharged patients in an attempt to reduce 30-day readmissions with mixed results. OBJECTIVE: To assess whether home 30-day telemonitoring after discharge for patients at high risk of readmission would reduce readmissions or mortality. DESIGN: Prospective, randomized controlled trial. PATIENTS: We compared 30-day readmission rates and mortality for patients at high risk for readmission who received home telemonitoring versus standard care between November 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…This initiative has been expanded to accept HF patients being discharged from the ED and from the hospital. Prior research has indicated possible reductions in readmissions as a result of postdischarge telemonitoring 18. Our ED and inpatient teams have indicated an ability to discharge patients sooner due to the close outpatient follow-up and reliable team structure provided by this programme.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This initiative has been expanded to accept HF patients being discharged from the ED and from the hospital. Prior research has indicated possible reductions in readmissions as a result of postdischarge telemonitoring 18. Our ED and inpatient teams have indicated an ability to discharge patients sooner due to the close outpatient follow-up and reliable team structure provided by this programme.…”
Section: Resultsmentioning
confidence: 97%
“…Prior research has indicated possible reductions in readmissions as a result of postdischarge telemonitoring. 18 Our ED and inpatient teams have indicated an ability to discharge patients sooner due to the close outpatient follow-up and reliable team structure provided by this programme. An HF hub was created for this programme expansion where RNs are only assigned HF patients and have fewer patients assigned to them because of the increased workload.…”
Section: Resultsmentioning
confidence: 99%
“…This review included three RCTs that investigated the effectiveness of the telemonitoring intervention [25,27,34]. Fredrix et al's [27] were disqualified from the meta-analysis since they reported the number of days lost owing to hospital readmission rather than the actual number of readmissions.…”
Section: Effect Of Tcis On Hospital Readmissionsmentioning
confidence: 99%
“…ED visits were recorded as a result of the telemonitoring intervention by two RCTs [30,34], and as a result, they were both included in the meta-analysis depicted in Figure 5. A decrease in ED visits within 30 days of discharge has been concluded (RR, 0.62; 95% CI 0.42 to 0.94, p = 0.02).…”
Section: Effect Of Tci On Ed Visitsmentioning
confidence: 99%
See 1 more Smart Citation